Effective detection of ZnO in nicotine using butterfly wing scales - Thanachai Changcharoen; Thidsanu Apiphatnaphakul; Wasupon Watjanavarreerat; Kitsakorn Locharoenrat (My University, 2022)
This study aimed to elucidate the optical functions of naturally butterfly wing scales via precise control of morphology as an effective photonic sensor and confirm the content of metal oxide nanoparticles in surrounding nicotine. Metal oxide nanoparticles mixed with nicotine were deposited on the wing scales through the spin-coating method and hence investigated using optical microscopy and spectroscopy. Experimental results demonstrated that absorption intensities of ZnO and TiO2 mixed with nicotine on Danaus genutia were remarkably enhanced. Due to the relatively high concentration of zinc found in e-cigarette aerosol, the intensity of ZnO/nicotine modelled as aerosol adsorption on Danaus genutia, further held a certain linear relationship with the concentration of ZnO. The limit of detection of ZnO was as low as 1 nM. The working mechanism of our sensor was explained through the molecular adsorption after H-bond formation of ZnO/nicotine molecules as high-index materials on the wing scales of Danaus genutia without aggregation. This photonic sensor is an alternative to the present-day methods for the rapid test of ZnO content, which is very simple without complicated instrumentation. Furthermore, our method might become a starting point for the advancement of portable instruments for onsite ZnO detection.
Keywords: Structural Coloration; Neurobiology and Insect Physiology Research